A Sociological View of the Economy and the State: From Economy-State Dualism towards Economy-State Embeddedness - Markin, Maxim (Journal of Economic Sociology, 2015)
The book Economy and State: A Sociological Perspective written by Nina Bandelj and Elizabeth Sowers opposes an economy-state dualism approach to economy-state embeddedness theories. Bandelj and Sowers follow Polanyi’s intellectual tradition and analyze the economy as instituted process focusing on the roles of the state. This book explores such fields of interest as property (the state’s role in capitalist and socialist economies), money (the state’s role in monetary policy, government spending, and taxation), labor (the state’s role in redistribution and employment), firms (the state’s role in business and industry governance), development (the state’s role in advancing economic prosperity), and international and global economy (the state’s role in managing the territorial boundaries of economic transactions). Markin argues that the institutional approach that Bandelj and Sowers chose as a core approach for their book is very fruitful for macro-analysis but it is not very appropriate for micro-analysis. In his review, Markin focuses on the roles of the state in turning land, labor and capital into “fictitious commodities” and the state’s role in the social construction of economic institutions. As Bandelj and Sowers do not provide a micro-analysis of state regulation of markets, Markin discusses these issues with help of the papers written by other scholars.